Understanding Employee Ownership - Long, Richard J. (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Understanding Employee Ownership," by Corey Rosen and Karen M. Young.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employee ownership; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z